AFAP1 Is a Novel Downstream Mediator of TGF-β1 for CCN2 Induction in Osteoblasts. - Youngjin Cho; Rachel Silverstein; Max T Geisinger; Stephen Martinkovich; Holly Corkill; Jess M Cunnick; Sonia L Planey; John A Arnott (PLoS ONE, 2015)
BACKGROUND:CCN2 acts as an anabolic growth factor to regulate osteoblast differentiation and function. CCN2 is induced by TGF-β1 and acts as a mediator of TGF-β1 induced matrix production in osteoblasts and Src is required for CCN2 induction by TGF-β1; however, the molecular mechanisms that control CCN2 induction in osteoblasts are poorly understood. AFAP1 binds activated forms of Src and can direct the activation of Src in certain cell types, however a role for AFAP1 downstream of TGF-β1 or in osteoblats is undefined. In this study, we investigated the role of AFAP1 for CCN2 induction by TGF-β1 in primary osteoblasts. RESULTS:We demonstrated that AFAP1 expression in osteoblasts occurs in a biphasic pattern with maximal expression levels occurring during osteoblast proliferation (~day 3), reduced expression during matrix production/maturation (~day 14-21), an a further increase in expression during mineralization (~day 21). AFAP1 expression is induced by TGF-β1 treatment in osteoblasts during days 7, 14 and 21. In osteoblasts, AFAP1 binds to Src and is required for Src activation by TGF-β1 and CCN2 promoter activity and protein induction by TGF-β1 treatment was impaired using AFAP1 siRNA, indicating the requirement of AFAP1 for CCN2 induction by TGF-β1. We also demonstrated that TGF-β1 induction of extracellular matrix protein collagen XIIa occurs in an AFAP1 dependent fashion. CONCLUSIONS:This study demonstrates that AFAP1 is an essential downstream signaling component of TGF-β1 for Src activation, CCN2 induction and collagen XIIa in osteoblasts.